Evaluation of study competence in pupils between 12-14 years old - Rial Sánchez, Raquel (2002)
There are three main study areas of guidance needs for pupils in Compulsory Secondary Education (CSE) which are academic development, personal and social development and the area of professional career. The area of academic development is where the knowledge to be acquired by the pupils, attitudes towards efficient learning in schools and the skills of efficient study are inculcated, the latter being the objective of our study. The research was taken from a sample of 80 school children between twelve and sixteen years old in a Secondary School in Santiago of Compostela (Spain). After analysing the results obtained we can see several motivations that justify the need to improve learning and study skills used by pupils. Normative arguments exist, needs that are exhibited by pupils and by teachers, especially tutors, of a scientific nature (connection with academic work) and to develop new strategies taking into account the contributions to the pedagogic research in this field. In this sense the application of an innovative programme of skills and study strategies in communication could be of interest.